1970
DOI: 10.1037/h0030112
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of behavior rehearsal in assertive training.

Abstract: A standardized, scmiaulomated, behavior rehearsal treatment procedure was developed, and two variations of this procedure, one with performance feedback and one without, were compared with two control procedures, a placebo therapy, and a no-treatment condition, in training 42 5s to be more assertive. Behavorial, selfreport, and psychophysiological laboratory measures, as well as an unobtrusive in vivo assertive test, revealed that the two behavior rehearsal procedures resulted in significantly greater improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
0
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(113 citation statements)
references
References 14 publications
4
108
0
1
Order By: Relevance
“…McFall and Marston (1970) found that transfer effects occurred on one of five measures in a telephone follow-up resistance to a magazine salesman. McFall and Lillesand (1971) failed to show a significant difference between treatment and assessment-placebo control groups in their telephone follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McFall and Marston (1970) found that transfer effects occurred on one of five measures in a telephone follow-up resistance to a magazine salesman. McFall and Lillesand (1971) failed to show a significant difference between treatment and assessment-placebo control groups in their telephone follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In treating nonassertive subjects, McFall and Marston (1970) found that behavior rehearsal resulted in a reduction in heart rate measured after McFalFs Behavior Rehearsal Assertion Test (BRAT); control groups demonstrated an increase in heart rate. Since a reduction in heart rate appears to be an outcome of McFall's treatment program, it has been used as the physiological measure in the present study.…”
mentioning
confidence: 99%
“…Social skills including assertiveness (McFall & Marston, 1970), positive heterosocial skills (Arkowitz, Lichtenstein, McGovern, & Hines, 1975), and job interview skills (Hollandsworth, Glazesk, & Dressel, 1978) have been trained for use in a variety of situtations. In addition, social skill training has been conducted with such diverse client populations as chronic schizophrenics (Bellack, Hersen, & Turner, 1976), mentally retarded adults (Hall, Sheldon-Wildgen, & Sherman, 1980), predelinquents (Braukmann, Maloney, Fixsen, Phillips, & Wolf, 1974), psychiatric patients (Furman, Geller, Simon, & Kelly, 1979), and the economically disadvantaged (Barbee & Keil, 1973).…”
Section: Teaching Job-related Social Skills To Learning Disabled Adolmentioning
confidence: 99%
“…Therapies such as assertive training that are aimed at ameliorating clients' and patients' social-skill deficits have been carefully evaluated both in analogue studies (e.g., Hersen, Eisler, Miller, Johnson, and Pinkston, 1973;Kazdin, 1974;McFall and Marston, 1970) and in clinically oriented investigations using group comparison designs (e.g., Percell, Berwick, and Beigel, 1974) and single case experimental strategies (e.g., Hersen, Turner, Edelstein, and Pinkston, 1975 Lillesand, 1971;McFall and Marston, 1970;McFall and Twentyman, 1973) and by Hersen and his colleagues with unassertive psychiatric inpatients . In addition, specific strategies for remediating dating-skill deficiencies in college students have been evaluated (e.g., Christensen and Arkowitz, 1974;Curran, 1975;Curran and Gilbert, 1975;Twentyman and McFall, 1975).…”
mentioning
confidence: 99%